IgG2 rules: N-acetyl-β-D-glucosamine-specific IgG2 and Th17/Th1 cooperation may promote the pathogenesis of acute rheumatic heart disease and be a biomarker of the autoimmune sequelae of Streptococcus pyogenes - Kirvan, Christine A.; Canini, Heather; Swedo, Susan E.; Hill, Harry; Veasy, George; Jankelow, David; Kosanke, Stanley; Ward, Kent; Zhao, Yan D.; Alvarez, Kathy; Hedrick, Andria; Cunningham, Madeleine W. (Frontiers in Cardiovascular Medicine, 2023)
Antecedent group A streptococcal pharyngitis is a well-established cause of acute rheumatic fever (ARF) where rheumatic valvular heart disease (RHD) and Sydenham chorea (SC) are major manifestations. In ARF, crossreactive antibodies and T cells respond to streptococcal antigens group A carbohydrate and M protein, and through molecular mimicry target heart and brain tissues. In this translational human study, we further address questions regarding specific pathogenic humoral and cellular immune mechanisms leading to streptococcal sequelae. Specifically, we investigate the immunoglobulin G (IgG) subclasses to better understand pathogenesis and how the streptococcal antigen, N acetyl-beta-D-glucosamine (GlcNAc), the immunodominant epitope of the group A carbohydrate, could contribute to disease in a susceptible host. In RHD and SC, serum IgG2 reacted significantly with GlcNAc, and distinguished ARF from uncomplicated pharyngitis. In SC, IgG2 in cerebrospinal fluid (CSF) selectively targeted human neuronal cells as well as GlcNAc. In rheumatic carditis, the IgG2 subclass preferentially deposited in valve tissues despite elevated concentrations of IgG1 and IgG3 to group A streptococcal M protein in RHD sera. Our novel human study demonstrates a strong IgG2 autoantibody response against GlcNAc in RHD and SC which targeted heart valves and neuronal cells and was identified with an IL-17A/IFN cooperative signature. GlcNAc-specific IgG2 may be an important autoantibody in pathogenesis of group A streptococcal sequelae and may serve as a biomarker for risk or development of rheumatic valvular heart disease.